"Nobody's Children"? Political Responses to the Homecoming of First World War Veterans in Northern and Southern Ireland, 1918–1929. (July 2021) - Destenay, Emmanuel
Abstract: At the time when Irish veterans of the Great War were being demobilized, Ireland was in a period of profound social, political, and cultural change that was irreversibly transforming the island. Armistice and the veterans' relief at having survived the conflict and being back with family could not eclipse the overwhelming political climate they met on their homecoming. This article draws on the 1929 Report by the Committee on Claims of British Ex-servicemen, commissioned by the Irish Free State to investigate whether Irish veterans were discriminated against by the Southern Irish and British authorities. The research also makes use of a range of underexploited primary sources: the Liaison and Evacuation Papers in the Military Archives in Dublin, the collection of minutes of the Irish Sailors' and Soldiers' Land Trust in the National Archives in London, and original material from the Public Record Office of Northern Ireland and the National Archives of Ireland relating to economic programs for veterans. A comparative approach of to the respective demobilizations of veterans in Northern and Southern Ireland in the 1920s reveals that disparities in formal recognition of their sacrifice and in special provision for housing and employment significantly and painfully complicated their repatriation.